2015
DOI: 10.1080/15222055.2015.1024362
|View full text |Cite
|
Sign up to set email alerts
|

Optimal Feeding Level of Burbot Larvae Fed Artemia spp. and Reared under Controlled Conditions

Abstract: The aim of this study was to determine the optimal feeding level of Burbot Lota lota larvae fed freshly hatched brine shrimp Artemia spp. nauplii during three different rearing periods: (1) 22–34 d posthatch (DPH), (2) 34–46 DPH, and (3) 46–58 DPH. The 36‐d experiment was performed in an experimental recirculating aquaculture system in 1‐L tanks. The stocking density was 100 individuals/L during the first and the second period, and 50 individuals/L during the third period. Temperature was 17.0 ± 0.1°C, and the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 46 publications
0
3
0
Order By: Relevance
“…The timing of weaning was found to be the most important factor for peled larvae feeding. Timing of the start of the weaning phase has also been found to be major factor in other fish species like pikeperch Sander lucioperca , totoaba Totoaba macdonaldi , burbot Lota lota, golden pompano Trachinotus ovatus or butter catfish Ompok bimaculatus (Hamza et al., ; Ma et al., ; Mata‐Sotres et al., ; Palinska‐Zarska et al., , ; Pradhan et al., ). It should be concluded that co‐feeding duration does not bring any advantage to peled larviculture.…”
Section: Discussionmentioning
confidence: 99%
“…The timing of weaning was found to be the most important factor for peled larvae feeding. Timing of the start of the weaning phase has also been found to be major factor in other fish species like pikeperch Sander lucioperca , totoaba Totoaba macdonaldi , burbot Lota lota, golden pompano Trachinotus ovatus or butter catfish Ompok bimaculatus (Hamza et al., ; Ma et al., ; Mata‐Sotres et al., ; Palinska‐Zarska et al., , ; Pradhan et al., ). It should be concluded that co‐feeding duration does not bring any advantage to peled larviculture.…”
Section: Discussionmentioning
confidence: 99%
“…Such finding was not observed in burbot larvae, which showed increased larval growth and survival with increasing ration level (Wocher et al., 2011). Estimating minimum feeding levels is critical since feeding larvae with live food prey entails high costs (Baskerville‐Bridges & Kling, 2000; Palińska‐Żarska et al., 2015). In the present study, a feeding level of 5 nauplii/mL at day 7 resulted in significantly higher body weight, suggesting that larvae benefitted from high feeding levels at this period, but did not affect larval performance during the rest of the feeding period.…”
Section: Discussionmentioning
confidence: 99%
“…At the onset of exogenous feeding its digestive system is only poorly developed (Lahnsteiner, 2016) and larvae require live feed as e.g. zooplankton (Lahnsteiner, Kletzl, & Weismann, 2012a) or Artemia (Wocher, Harsányi, & Schwarz, 2012;Palińska-Żarska, Żarski, Krejszeff, Kupren, Łączyńska, & Kucharczyk, 2015). Therefore, weaning to artificial dry feed is necessary when fish are reared for aquaculture purposes.…”
Section: Introductionmentioning
confidence: 99%